Efektivitas Bangunan Pemecah Gelombang Dalam Pengendalian Abrasi Pantai di Kecamatan Biduk-Biduk - Maryadi; Setyasih, Iya; Anwar, Yaskinul (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2020)
Abrasion is a problem that often occurs in the coastline, therefore this problem must be addressed immediately, it makes the special attention of the district government. Big Dipper in handling abrasion that has occurred at several locations. This study aims to determine how the potential for abrasion, mitigation efforts and how the effectiveness of the breakwater in reducing abrasion in Biduk-Biduk District. This research was conducted with a purposive sampling method and data analysis techniques used include analysis of abrasion potential, analysis of efforts to overcome abrasion and analysis of the effectiveness of building waves as an effort to obtain supporting data such as shoreline change data, breakwater building data, data factors affecting the abrasion and effectiveness of building breakwaters obtained from the District, Public Works Agency and the Berau District Government Fund. the results of abrasion potential studies in Biduk-Biduk Subdistrict indicate that there are still many areas that have experienced severe abrasion and have not received abrasion countermeasures, as well as the efforts made to cope with abrasion areas in the Biduk-Biduk Subdistrict. Now there are quite a variety of them, including breakwater structures, coastal walls, offshore structures , groyne buildings, ovaled beach wall buildings and embankment beach wall buildings. the effectiveness of wave-breaking buildings in this area can be said to have not functioned optimally so that many buildings are less effective in dealing with abrasion.